Kesulitan-Kesulitan yang Dihadapi Lansia dalam Mengikuti Program Penyuluhan Kesehatan pada Kelompok Lansia â€œManggisâ€, Padang - Murni, Murni; Ismaniar, Ismaniar (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
This research is motivated by the phenomenon of the low participation of the elderly in taking part in the health education program for the elderly "Manggis" in Gunung Sarik, Kuranji, Padang. This is evidenced by the elderly health of the elderly in attending health education. The researcher suspects the causes of the low participation of the elderly in the Gunung Sarik, Kuranji, Padang. This type of research is quantitative descriptive research. The population in this study was 33 students who attended computer technician training. The sampling technique used was purposive random sampling. Samples were taken as much as 75% of the population, totaling 33 people. The technique of collecting data uses a questionnaire. While the data collection tools list of statements. The data analysis technique uses the percentage formula. The results showed that the difficulties faced by the elderly in participating in the health education program in the "Manggis" elderly physical and psychological aspects of the Gunung Sarik Subdistrict, Kuranji District, Padang were categorized as high. This is evidenced by the majority of the elderly claiming often. So it can be said that the absence of the elderly following the counseling program was caused by the psychological condition of the elderly themselves who were not good enough.